Current Challenges and Future Directions in Handling Stroke Patients With Patent Foramen Ovale—A Brief Review - Huber, Charlotte; Wachter, Rolf; Pelz, Johann; Michalski, Dominik (Frontiers in Neurology, 2022)
The role of patent foramen ovale (PFO) in stroke was debated for decades. Randomized clinical trials (RCTs) have shown fewer recurrent events after PFO closure in patients with cryptogenic stroke (CS). However, in clinical practice, treating stroke patients with coexisting PFO raises some questions. This brief review summarizes current knowledge and challenges in handling stroke patients with PFO and identifies issues for future research. The rationale for PFO closure was initially based on the concept of paradoxical embolism from deep vein thrombosis (DVT). However, RCTs did not consider such details, limiting their impact from a pathophysiological perspective. Only a few studies explored the coexistence of PFO and DVT in CS with varying results. Consequently, the PFO itself might play a role as a prothrombotic structure. Transesophageal echocardiography thus appears most appropriate for PFO detection, while a large shunt size or an associated atrial septum aneurysm qualify for a high-risk PFO. For drug-based treatment alone, studies did not find a definite superiority of oral anticoagulation over antiplatelet therapy. Remarkably, drug-based treatment in addition to PFO closure was not standardized in RCTs. The available literature rarely considers patients with transient ischemic attack (TIA), over 60 years of age, and competing etiologies like atrial fibrillation. In summary, RCTs suggest efficacy for closure of high-risk PFO only in a small subgroup of stroke patients. However, research is also needed to reevaluate the pathophysiological concept of PFO-related stroke and establish strategies for older and TIA patients and those with competing risk factors or low-risk PFO.